Republic of Crimea and Sevastopol: First Results of Implementation of State Programs in Economic and Social Spheres - A. O. Znamenshchikov (Управленческое консультирование, 2019)
Having joined Russia, Crimea found itself in unique economic conditions. In a short period of time, the peninsula has to rebuild to new legislation and establish economic ties. After the reunification of Crimea with Russia in March 2014, large-scale projects aimed at modernizing Crimea ‘s economy and integrating it with the rest of Russia began. In 2014 Crimea received the status of a free economic zone. The Federal Target Program for Social and Economic Development of Crimea until 2022 has been developed and is being implemented. The program, in particular, includes the construction of electric grid facilities, including power bridge to Crimea and cable crossing through the Strait of Kerchen, construction of transport crossing through the Strait of Kerchen (Crimean Bridge) and the Federal Route Tavrida, a number of facilities of medicine and health care, water supply, development of industrial complex, social sphere, tourist and recreational clusters, etc. The article summarizes the first results of the implementation of a number of state programs in the economic and social spheres in the five years since the reunification of Crimea with the Russian Federation.